2020
DOI: 10.1007/s10209-020-00744-5
|View full text |Cite
|
Sign up to set email alerts
|

Toward Kinecting cognition by behaviour recognition-based deep learning and big data

Abstract: The majority of older people wish to live independently at home as long as possible despite having a range of age-related conditions including cognitive impairment. To facilitate this, there has been an extensive focus on exploring the capability of new technologies with limited success. This paper investigates whether MS Kinect (a motion-based sensing 3-D scanner device) within the MiiHome (My Intelligent Home) project in conjunction with other sensory data, machine learning and big data techniques can assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Finally, the classifier's accuracy, confusion matrix, and AUC evaluation metric showed that a better results with high confidence band and predictive capabilities obtained by our purposed methodologies for classification of modified leg velocity signals. Further works includes extending the application of this techniques toward Kinecting cognitive impairments [15] beside using amplitude modified signals and explore the expectation that AM might offer better capability to represent the spectral components of a low frequency signal than the FM technique when it comes to dealing with MS Kinect data that has medium/low data rate of 30 frames per second.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the classifier's accuracy, confusion matrix, and AUC evaluation metric showed that a better results with high confidence band and predictive capabilities obtained by our purposed methodologies for classification of modified leg velocity signals. Further works includes extending the application of this techniques toward Kinecting cognitive impairments [15] beside using amplitude modified signals and explore the expectation that AM might offer better capability to represent the spectral components of a low frequency signal than the FM technique when it comes to dealing with MS Kinect data that has medium/low data rate of 30 frames per second.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons and perceptron models: The concept of neurons comes from biology. A simple neuron usually consists of several dendrites, an axon, and several axon-ends (Soufian et al, 2022). Among them, dendrites are mainly used to receive input information, axon ends transmit information to the next neuron, and axons are used to connect dendrites and axon ends (Yu et al, 2022).…”
Section: Model Structure Of Deep Learningmentioning
confidence: 99%